2005
DOI: 10.1148/radiol.2353040280
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Lung-to-Liver Signal Intensity Ratio at MR Imaging: Development of a Normal Scale and Possible Role in Predicting Pulmonary Hypoplasia in Utero

Abstract: This study provides a normal scale with a 95% prediction interval for LLSIR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 16 publications
4
39
0
1
Order By: Relevance
“…Therefore, we selected the liver as a reference. In fact, the LLSIR for normal lung also increased with GA in our analysis as well as in a previous study (16). Keller et al (3) reported that the lung/liver SI ratio in cases with thoracic abnormality did not differ significantly from that in the normal population.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Therefore, we selected the liver as a reference. In fact, the LLSIR for normal lung also increased with GA in our analysis as well as in a previous study (16). Keller et al (3) reported that the lung/liver SI ratio in cases with thoracic abnormality did not differ significantly from that in the normal population.…”
Section: Discussionsupporting
confidence: 87%
“…Although the liver seems to be inappropriate as a reference organ, the MR sequence is quite different from ours using T2-weighted imaging, and no evaluation of the SI ratio after 26 weeks of gestation was made. On the other hand, Brewerton et al (16) reported that the LLSIR for normal lung increases with GA on HASTE and that there is a marked difference in LLSIR between normal and hypoplastic lungs at 25 or more weeks of gestation. The SI loss due to a difference in distance from the phased-array coil also can be avoided because the liver is located near the fetal lung.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the potential of MR imaging to characterise the chemical and structural composition of different tissue types, attempts have been made to use signal intensity measurements on different sequences to assess developmental changes associated with biochemical maturation processes [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Low MRI intensity in T2-weighted image is thought to be a sign of pulmonary hypoplasia clinically, 17,18 and animal study also showed it. 19 However, the meaning of MRI signal intensity of the CDH lung remains controversial.…”
Section: Discussionmentioning
confidence: 95%